Preparation method of denitration catalyst
By optimizing the catalyst preparation process and the synergistic effect of using triethylenediamine and HPMA, the problems of denitrition efficiency of traditional catalysts and side reactions of SO2 oxidation during low load operation are solved, and efficient denitrification and low SO2 oxidation rates are achieved, avoiding secondary pollution.
Patent Information
- Application Number
- CN202411829255.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional SCR catalysts have reduced reaction activity and decreased denitrification efficiency during low load operation, and it is difficult to effectively inhibit the side reaction of SO2 oxidation, resulting in excess of nitrogen oxide emissions and secondary pollution.
By optimizing the catalyst preparation process, the active components are evenly dispersed on the support surface. The synergistic action of triethylenediamine and HPMA is used to optimize the structure and acidity of the catalyst surface to inhibit the SO2 oxidation reaction.
It improves the denitrification efficiency during low-load operation, inhibits the side reaction of SO2 oxidation, reduces the SO2 oxidation rate, avoids secondary pollution, and ensures the stable performance of the catalyst under high SO2 concentration conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of denitration catalysts, and more specifically, to a method for preparing a denitration catalyst. Background Art
[0002] In recent years, as the national environmental protection policies have become increasingly stringent, domestic power generation companies have actively responded and orderly promoted the transformation and upgrading of environmental protection facilities, striving to achieve ultra-low emissions of atmospheric pollutants. Especially in the field of denitrification technology for coal-fired power units, traditional selective catalytic reduction (SCR) systems play a key role in treating nitrogen oxide (NOx) emissions. However, with the increasing proportion of power generation from renewable energy sources such as wind power and photovoltaics, coal-fired power units are facing increasing pressure for deep peak regulation and start-stop peak regulation, resulting in long-term low-load operation of the units, which significantly reduces the flue gas temperature. The lower flue gas temperature reduces the reaction activity of traditional SCR catalysts and significantly reduces the denitrification efficiency, which may lead to excessive nitrogen oxide emissions and increase environmental pollution.
[0003] In terms of catalyst design, the wall thickness of the extruded honeycomb catalyst commonly used in the current market is generally between 0.5 and 1.5 mm. Due to the limitations of the catalyst preparation process, the effective active ingredients are usually evenly distributed in the thick wall part. However, the denitrification reaction mainly occurs in the area within 0.1 mm on the catalyst surface. The part with a wall thickness of more than 0.1 mm hardly participates in the denitrification reaction. Instead, it may promote the oxidation side reaction of SO2, reducing the active utilization rate of the catalyst. Therefore, how to improve the utilization rate of the active ingredients of the catalyst and reduce the ineffective part of the non-reactive area has become the key to improving the denitrification efficiency and reducing secondary pollution.
[0004] In addition, existing catalyst technology is relatively stable in meeting the SO2 oxidation rate requirements of traditional thermal power plants, and can usually control the SO2 oxidation rate below 1%. However, in order to reduce fuel costs, some thermal power plants burn low-quality coal with high sulfur content, which leads to an increase in the concentration of sulfur oxides in the flue gas; in the non-electric field, due to the complex types of fuels and poor stability, the SO2 concentration in the flue gas is also high. In this case, it is difficult for traditional catalysts to meet the denitrification efficiency under low load conditions and effectively inhibit the increase in SO2 oxidation rate under the operating conditions of deep peak regulation of coal-fired power units, which further limits the application scope and efficiency of the catalyst. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present invention proposes a method for preparing a denitration catalyst, which optimizes the catalyst preparation process to uniformly disperse the active components on the carrier surface, thereby improving the denitration efficiency during low-load operation, effectively inhibiting the SO2 oxidation side reaction, reducing the SO2 oxidation rate, and avoiding the occurrence of secondary pollution.
[0006] The technical solution adopted by the present invention is to provide a method for preparing a denitration catalyst, which specifically comprises the following steps:
[0007] S1, dissolving AMV, AMT and ammonium paramolybdate respectively to obtain corresponding solutions;
[0008] S2, mixing the ammonium paramolybdate solution and the AMT solution, adding triethylenediamine and dispersant A, stirring and mixing to obtain a mixed solution A;
[0009] S3, adding mixed solution A to the AMV solution, and continuing to stir to form mixed solution B;
[0010] S4. Add the mixed solution B to the catalyst carrier, and obtain a finished catalyst unit through drying and calcination.
[0011] After adopting the above structure, the mixed active components are more evenly dispersed, easier to disperse to the carrier surface, and the reaction temperature is wider. The catalyst preparation method of the present invention not only solves the problem of reduced catalyst activity during low-load operation, but also achieves remarkable results in inhibiting SO2 oxidation side reactions. By rationally regulating the component ratio and preparation process of the catalyst, the SO2 oxidation rate can be effectively reduced, ensuring the efficiency of the denitration reaction while avoiding the secondary pollution problem that may occur with traditional catalysts under high SO2 concentration conditions.
[0012] According to one embodiment of the present invention, when the preparation method adopts an integral extruded catalyst, the step S4 specifically comprises:
[0013] S41, pouring the mixed solution B into the titanium dioxide and continuing to stir to obtain a uniform mass structure, and then sequentially performing aging, die extrusion molding, drying, and calcination to obtain a finished catalyst unit;
[0014] First, slowly add the mixed solution B to the titanium dioxide, and ensure that the liquid and solid are in full contact during the stirring process, so that the active components in the solution are evenly dispersed on the surface of the titanium dioxide to form a uniform mass structure. At this time, the titanium dioxide not only serves as a carrier of the catalyst, but also provides more reaction sites through its high surface area, promotes the uniform distribution of active components, and provides better support for subsequent catalytic reactions.
[0015] Secondly, the obtained agglomerate structure is aged so that the water in the agglomerate material gradually evaporates and reaches the appropriate plasticity to facilitate subsequent die extrusion molding. In this process, the particle and structural stability of the material is enhanced, and the distribution of the active components on the carrier surface is further consolidated. The agglomerate material after aging has appropriate fluidity and adhesion, and can be extruded through a die to form the desired shape, such as a honeycomb or columnar catalyst unit.
[0016] The formed catalyst unit is dried to remove excess water for subsequent calcination.
[0017] Finally, the dried catalyst unit is sintered under high temperature conditions through a calcination process to improve its mechanical strength and thermal stability. Temperature control during the calcination process is crucial, and the curing of the active components of the catalyst and the structural stability of the catalyst carrier must be promoted within a suitable temperature range. Calcination not only helps the formation of active components, but also further promotes the optimization of the catalyst surface structure, giving it a better specific surface area and reaction performance.
[0018] According to one embodiment of the present invention, when the preparation method adopts an impregnation catalyst, the step S4 specifically includes:
[0019] S42, immersing the catalyst substrate into the mixed solution B through ultrasonic impregnation, and then taking out, drying, and calcining in sequence to obtain a finished catalyst unit.
[0020] According to one embodiment of the present invention, the dispersant A is at least one of fatty alcohol polyoxyethylene ether, polyethylene glycol, HPMA, and monoethanolamine.
[0021] According to an embodiment of the present invention, the step S1 specifically includes:
[0022] S11. Mix AMV and triethanolamine, and add deionized water to fully dissolve to prepare an AMV solution.
[0023] S12, adding AMT to deionized water to fully dissolve AMT to prepare an AMT solution;
[0024] S13, mixing ammonium paramolybdate and phosphoric acid, adding deionized water to fully dissolve to prepare an ammonium metamolybdate solution.
[0025] According to an embodiment of the present invention, in step S11, the mass ratio of triethanolamine to active ingredient is: 1-50:100; the mass of the active ingredient is specifically the sum of the masses of the three active ingredients AMV, AMT and ammonium paramolybdate.
[0026] According to one embodiment of the present invention, in step S2, the mass ratio of triethylenediamine to active ingredient is: 1-50:100; the mass of the active ingredient is specifically the sum of the masses of the three active ingredients AMV, AMT and ammonium paramolybdate.
[0027] According to one embodiment of the present invention, in step S2, the mass ratio of dispersant A to active ingredient is: 1-50:100; the mass of the active ingredient is specifically the sum of the masses of the three active ingredients AMV, AMT and ammonium paramolybdate.
[0028] According to one embodiment of the present invention, the dispersant A is HPMA; when HPMA (hydrolyzed polymaleic anhydride) and triethylenediamine work together, the two can form a synergistic effect in the catalyst synthesis process. HPMA provides good metal ion complexing and dispersion capabilities through its carboxyl and ester functional groups, while triethylenediamine further enhances the stability and dispersibility of the active components and avoids uneven distribution of metal ions on the carrier. This synergistic effect ensures a high specific surface area and good reaction activity of the catalyst, thereby maintaining a high denitration efficiency under deep peak regulation and low load operation conditions of coal-fired power units.
[0029] In addition, the synergistic effect of HPMA and triethylenediamine is also reflected in SO2 inhibition. By optimizing the structure and acidity and alkalinity of the catalyst surface, the oxidation reaction of SO2 can be effectively reduced, thereby controlling the increase of the SO2 oxidation rate, avoiding the side reaction of the catalyst under high SO2 concentration conditions, and reducing the emission of secondary pollution. This characteristic enables the catalyst of the present invention to maintain a low SO2 oxidation rate while meeting the strict denitration requirements, providing a more efficient and stable solution for the environmental protection transformation of coal-fired power units.
[0030] According to one embodiment of the present invention, in step S3, the mixed solution A is added to the AMV solution, and stirring is continued at 40° C. to form a mixed solution B. DETAILED DESCRIPTION
[0032] Embodiment 1
[0033] The carrier is prepared by using the traditional monolithic extrusion catalyst preparation method: titanium dioxide is used as the main carrier, and deionized water accounting for 20wt%-40wt% of the mass of titanium dioxide is added, and stirring is continued. In addition, the active ingredient AMV is dissolved in an aqueous solution of triethanolamine, AMT is dissolved in deionized water, and ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, triethylenediamine and HPMA are added, and the mixture is stirred and mixed at 40°C for 30min, and the speed is controlled at 300r / min. Then the mixed solution is added to the AMV solution, and stirring is continued for 10min to form a new mixed solution. The mixed solution is poured into the titanium dioxide and stirred. Until the raw material composition changes from powder and liquid state to a uniform "dough" state, which meets the requirements of subsequent extrusion. After the dough is aged for 24h, it is extruded into a mold, and the formed catalyst is dried at 105°C for 4h, and calcined at 550°C for 4h to obtain a comparative sample catalyst finished unit.
[0034] The addition amount of each component is AMV: AMT: ammonium paramolybdate = 1: 2: 2, and the three components account for 1%, 2%, and 2% of the total mass of titanium dioxide respectively;
[0035] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0036] AMT: water dissolving AMV = 1:2;
[0037] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0038] Triethylenediamine:HPMA=1:4, the added amount of triethylenediamine is 1% of the mass of titanium dioxide.
[0039] Embodiment 2
[0040] The carrier is prepared by using the traditional integral extrusion catalyst preparation method: titanium dioxide is used as the main carrier, 20wt%-40wt% deionized water is added, and stirring is continued. In addition, the active ingredient AMV is dissolved in triethanolamine, AMT is dissolved in deionized water, and ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, triethylenediamine and fatty alcohol polyoxyethylene ether are added, and the mixture is stirred and mixed at 40°C for 30min, and the speed is controlled at 300r / min. Then the mixed solution is added to the AMV solution, and stirring is continued for 10min to form a new mixed solution. The mixed solution is poured into the titanium dioxide and stirred. Until the raw material composition changes from powder and liquid state to a uniform "dough" state, which meets the requirements of subsequent extrusion. After the dough is aged for 24h, it is extruded into a mold, and the formed catalyst is dried at 105°C for 4h, and calcined at 550°C for 4h to obtain a comparative sample catalyst finished unit.
[0041] The addition amount of each component is AMV: AMT: ammonium paramolybdate = 1: 2: 2, and the three components account for 1%, 2%, and 2% of the total mass of titanium dioxide respectively;
[0042] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0043] AMT: water dissolving AMV = 1:2;
[0044] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0045] Triethylenediamine: fatty alcohol polyoxyethylene ether = 1:4, the amount of triethylenediamine added is 1% of the mass of titanium dioxide.
[0046] Embodiment 3
[0047] The carrier is prepared by using the traditional integral extrusion catalyst preparation method: titanium dioxide is used as the main carrier, 20wt%-40wt% deionized water is added, and stirring is continued. In addition, the active ingredient AMV is dissolved in triethanolamine, AMT is dissolved in deionized water, and ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, triethylenediamine and polyethylene glycol are added, and the mixture is stirred and mixed at 40°C for 30 minutes, and the speed is controlled at 300r / min. Then the mixed solution is added to the AMV solution, and stirring is continued for 10 minutes to form a new mixed solution. The mixed solution is poured into the titanium dioxide and stirred. Until the raw material composition changes from powder and liquid state to a uniform "dough" state, which meets the requirements of subsequent extrusion. After the dough is aged for 24 hours, it is extruded into a mold, and the formed catalyst is dried at 105°C for 4 hours, and calcined at 550°C for 4 hours to obtain a comparative sample catalyst finished unit.
[0048] The addition amount of each component is AMV: AMT: ammonium paramolybdate = 1: 2: 2, and the three components account for 1%, 2%, and 2% of the total mass of titanium dioxide respectively;
[0049] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0050] AMT: water dissolving AMV = 1:2;
[0051] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0052] Triethylenediamine: polyethylene glycol = 1:4, the amount of triethylenediamine added is 1% of the mass of titanium dioxide.
[0053] Comparative Example 1
[0054] The carrier is prepared using the traditional integral extrusion catalyst preparation method: titanium dioxide is used as the main carrier, 20wt%-40wt% deionized water is added, and stirring is continued. During the stirring process, the active ingredient AMV is dissolved in triethanolamine, AMT and ammonium paramolybdate are dissolved in deionized water, and the liquids are poured in order until the raw material composition changes from powder and liquid to a uniform "dough" state, which meets the requirements of subsequent extrusion. The dough is aged for 24 hours and then extruded into a mold. The molded catalyst is dried at 105°C for 4 hours and calcined at 550°C for 4 hours to obtain a finished catalyst unit.
[0055] The addition amount of each component is AMV: AMT: ammonium paramolybdate = 1: 2: 2, and the three components account for 1%, 2%, and 2% of the total mass of titanium dioxide respectively;
[0056] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0057] AMT: water dissolving AMV = 1:2;
[0058] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4.
[0059] Comparative Example 2
[0060] The carrier is prepared by using the traditional integral extrusion catalyst preparation method: titanium dioxide is used as the main carrier, 20wt%-40wt% deionized water is added, and stirring is continued. In addition, the active ingredient AMV is dissolved in triethanolamine, AMT is dissolved in deionized water, and ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, triethylenediamine is added, and the mixture is stirred and mixed at 40°C for 30 minutes, and the speed is controlled at 300r / min. Then the mixed solution is added to the AMV solution, and stirring is continued for 10 minutes to form a new mixed solution. The mixed solution is poured into the titanium dioxide and stirred. Until the raw material composition changes from powder and liquid state to a uniform "dough" state, which meets the requirements of subsequent extrusion. After the dough is aged for 24 hours, it is extruded into a mold, and the formed catalyst is dried at 105°C for 4 hours, and calcined at 550°C for 4 hours to obtain a comparative sample catalyst finished unit.
[0061] The addition amount of each component is AMV: AMT: ammonium paramolybdate = 1: 2: 2, and the three components account for 1%, 2%, and 2% of the total mass of titanium dioxide respectively;
[0062] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0063] AMT: water dissolving AMV = 1:2;
[0064] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0065] The amount of triethylenediamine added is 1% of the mass of titanium dioxide.
[0066] Comparative Example 3
[0067] The carrier is prepared by using the traditional integral extrusion catalyst preparation method: titanium dioxide is used as the main carrier, 20wt%-40wt% deionized water is added, and stirring is continued. In addition, the active ingredient AMV is dissolved in triethanolamine, AMT is dissolved in deionized water, and ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, HPMA is added, and the mixture is stirred at 40°C for 30 minutes, and the speed is controlled at 300r / min. Then the mixed solution is added to the AMV solution, and stirring is continued for 10 minutes to form a new mixed solution. The mixed solution is poured into the titanium dioxide and stirred. Until the raw material composition changes from powder and liquid state to a uniform "dough" state, which meets the requirements of subsequent extrusion. After the dough is aged for 24 hours, it is extruded into a mold, and the formed catalyst is dried at 105°C for 4 hours, and calcined at 550°C for 4 hours to obtain a comparative sample catalyst finished unit.
[0068] The addition amount of each component is AMV: AMT: ammonium paramolybdate = 1: 2: 2, and the three components account for 1%, 2%, and 2% of the total mass of titanium dioxide respectively;
[0069] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0070] AMT: water dissolving AMV = 1:2;
[0071] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0072] The amount of HPMA added is 4% of the mass of titanium dioxide.
[0073] The surface active components of the catalyst product units of Examples 1-3 and Comparative Examples 1-3 were measured using an X-ray fluorescence spectrometer XRF, model S8 TIGER|Bruker, and the measurement results are as follows:
[0074] sample <![CDATA[TIO2 / %]]> <![CDATA[V2O5 / %]]> <![CDATA[WO3 / %]]> <![CDATA[MoO3 / %]]> Example 1 87.877 1.105 2.208 2.124 Example 2 87.846 1.050 2.103 2.015 Example 3 87.745 1.049 2.153 2.113 Comparative Example 1 87.936 0.986 2.012 1.908 Comparative Example 2 87.865 1.003 2.032 2.004 Comparative Example 3 87.753 1.014 2.050 2.063
[0075] Compared with Comparative Example 1, under the same amount of active ingredient added, the catalyst carrier treated by this method can allow more active ingredients to be loaded onto the surface of the catalyst unit.
[0076] Embodiment 4
[0077] The catalyst substrates without active components of different structures such as honeycomb and plate are ultrasonically impregnated in deionized water for 10 minutes; 3% AMV of active ingredients is dissolved in triethanolamine, 3% AMT is dissolved in deionized water, and 2% ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, triethylenediamine and HPMA are added, and the mixture is stirred at 40°C for 30 minutes, and the speed is controlled at 300r / min, and then the mixed solution is added to the AMV solution, and the stirring is continued for 10 minutes to form a new mixed solution; the catalyst substrate is placed in the mixed solution, ultrasonicated at 40°C for 10 minutes, and then taken out. The impregnated sample is dried at 105°C for 4 hours and calcined at 550°C for 4 hours to obtain the finished product.
[0078] Among them, 3% AMV, 3% AMT, and 2% ammonium paramolybdate refer to the percentage of the total mass of deionized water;
[0079] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0080] AMT: water dissolving AMV = 1:2;
[0081] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0082] Triethylenediamine:HPMA=1:4, the amount of triethylenediamine added is 1% of the total mass of deionized water.
[0083] Embodiment 5
[0084] The catalyst substrates without active components of different structures such as honeycomb and plate are ultrasonically impregnated in deionized water for 10 minutes; 3% AMV of active ingredients is dissolved in triethanolamine, 3% AMT is dissolved in deionized water, and 2% ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, triethylenediamine and monoethanolamine are added, and the mixture is stirred at 40°C for 30 minutes, and the speed is controlled at 300r / min, and then the mixed solution is added to the AMV solution, and the stirring is continued for 10 minutes to form a new mixed solution; the catalyst substrate is placed in the mixed solution, ultrasonicated at 40°C for 10 minutes, and then taken out. The impregnated sample is dried at 105°C for 4 hours and calcined at 550°C for 4 hours to obtain the finished product.
[0085] Among them, 3% AMV, 3% AMT, and 2% ammonium paramolybdate refer to the percentage of the total mass of deionized water;
[0086] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0087] AMT: water dissolving AMV = 1:2;
[0088] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0089] Triethylenediamine:monoethanolamine=1:4, the amount of triethylenediamine added is 1% of the total mass of deionized water.
[0090] Comparative Example 4
[0091] The catalyst substrates without active components of different structures such as honeycomb and plate were ultrasonically impregnated in deionized water for 10 minutes; 3% AMV, an active ingredient, was dissolved in triethanolamine, 3% AMT and 2% ammonium paramolybdate were dissolved in deionized water, and then the solutions were mixed and ultrasonically formed at 40°C to form a new solution; the catalyst substrate was placed in the mixed solution, ultrasonically treated at 40°C for 10 minutes, and then taken out. The impregnated sample was dried at 105°C for 4 hours and calcined at 550°C for 4 hours to obtain the finished product.
[0092] Among them, 3% AMV, 3% AMT, and 2% ammonium paramolybdate refer to the percentage of the total mass of deionized water;
[0093] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0094] AMT: water dissolving AMV = 1:2;
[0095] Ammonium paramolybdate: water in which ammonium paramolybdate is dissolved = 2:4.
[0096] Comparative Example 5
[0097] The catalyst substrates without active components of different structures such as honeycomb and plate are ultrasonically impregnated in deionized water for 10 minutes; 3% AMV of active ingredients is dissolved in triethanolamine, 3% AMT is dissolved in deionized water, and 2% ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, triethylenediamine is added, and the mixture is stirred at 40°C for 30 minutes, and the speed is controlled at 300r / min, and then the mixed solution is added to the AMV solution, and the stirring is continued for 10 minutes to form a new mixed solution; the catalyst substrate is placed in the mixed solution, ultrasonicated at 40°C for 10 minutes, and then taken out. The impregnated sample is dried at 105°C for 4 hours and calcined at 550°C for 4 hours to obtain the finished product.
[0098] Among them, 3% AMV, 3% AMT, and 2% ammonium paramolybdate refer to the percentage of the total mass of deionized water;
[0099] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0100] AMT: water dissolving AMV = 1:2;
[0101] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0102] The amount of triethylenediamine added was 1% of the total mass of deionized water.
[0103] Comparative Example 6
[0104] The catalyst substrates without active components of different structures such as honeycomb and plate are ultrasonically impregnated in deionized water for 10 minutes; 3% AMV of active ingredients is dissolved in triethanolamine, 3% AMT is dissolved in deionized water, and 2% ammonium paramolybdate and phosphoric acid are mixed and dissolved in deionized water. After the above three liquids are fully dissolved, the ammonium paramolybdate solution and the AMT solution are mixed, HPMA is added, and the mixture is stirred at 40°C for 30 minutes, and the speed is controlled at 300r / min, and then the mixed solution is added to the AMV solution, and the stirring is continued for 10 minutes to form a new mixed solution; the catalyst substrate is placed in the mixed solution, ultrasonicated at 40°C for 10 minutes, and then taken out. The impregnated sample is dried at 105°C for 4 hours and calcined at 550°C for 4 hours to obtain the finished product.
[0105] Among them, 3% AMV, 3% AMT, and 2% ammonium paramolybdate refer to the percentage of the total mass of deionized water;
[0106] AMV: triethanolamine: water dissolving AMV = 1:2:10;
[0107] AMT: water dissolving AMV = 1:2;
[0108] Ammonium paramolybdate: phosphoric acid: water in which ammonium paramolybdate is dissolved = 2:1:4;
[0109] The amount of HPMA added was 4% of the total mass of deionized water.
[0110] The surface active components of the catalyst product units of Examples 4-5 and Comparative Examples 4-6 were measured using an X-ray fluorescence spectrometer XRF, model S8 TIGER|Bruker, and the measurement results are as follows:
[0111] sample <![CDATA[V2O5 / %]]> <![CDATA[WO3 / %]]> <![CDATA[MoO3 / %]]> Example 4 1.125 1.008 1.985 Example 5 1.035 0.975 1.887 Comparative Example 4 0.983 0.895 1.753 Comparative Example 5 1.003 0.902 1.813 Comparative Example 6 1.012 0.913 1.765
[0112] Compared with Example 4, the catalyst carrier loaded by the impregnation method can also allow more active ingredients to be loaded onto the surface of the catalyst unit.
[0113] Test example
[0114] (1) Carry out flue gas experiments on the denitrification catalyst according to the experimental steps to test its SO2 oxidation rate and denitrification activity. The flue gas test conditions are unified as follows:
[0115]
[0116] The test temperature point is 300℃.
[0117] (2) The test results are as follows:
[0118] project <![CDATA[SO2 oxidation rate (%)]]> Denitrification rate (%) Example 1 0.62 93.33 Comparative Example 1 0.81 85.27 Comparative Example 2 0.71 87.21 Comparative Example 3 0.73 88.01 Example 4 0.90 84.74 Comparative Example 4 0.94 81.33 Comparative Example 5 0.93 83.27 Comparative Example 6 0.96 80.24
[0119] As shown in the table above, regardless of whether the catalyst carrier is prepared by the integral extrusion method or the impregnation method, the experimental samples prepared by this method are significantly better than the catalyst samples obtained by the traditional production method in terms of denitration performance. The SO2 oxidation rate of Example 1 is significantly lower than the national standard of 1.0%, and is much lower than the SO2 oxidation rate of the catalyst produced by the conventional method (Comparative Example 1). These experimental results show that this technology can effectively improve the performance of the active components in the catalyst.
[0120] Comparing the experimental results of Example 1 with Comparative Examples 2-3, in Example 1, triethylenediamine and HPMA were added simultaneously, while in Comparative Example 2, only triethylenediamine was added, and in Comparative Example 3, only HPMA was added. The SO2 oxidation rate of Example 1 was lower than that of Comparative Examples 2 and 3, and the denitration rate was also higher than that of the two comparative samples. This shows that the synergistic effect of triethylenediamine and HPMA plays a key role in the synthesis process of the catalyst and can optimize the performance of the catalyst.
[0121] Similarly, combining the results of Example 4 with Comparative Examples 5-6, Example 4 added both triethylenediamine and HPMA, while Comparative Example 5 only added triethylenediamine, and Comparative Example 6 only added HPMA. Example 4 had a lower SO2 oxidation rate than Comparative Example 5 and Comparative Example 6, and its denitration rate was also higher than both. This further proves that the combined effect of HPMA and triethylenediamine can significantly improve the performance of the catalyst, forming a synergistic effect.
[0122] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0123] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a denitration catalyst, characterized in that: The specific steps include: S1, dissolving AMV, AMT and ammonium paramolybdate respectively to obtain corresponding solutions; S2, mixing the ammonium paramolybdate solution and the AMT solution, adding triethylenediamine and dispersant A, stirring and mixing to obtain a mixed solution A; S3, adding mixed solution A to the AMV solution, and continuing to stir to form mixed solution B; S4. Add the mixed solution B to the catalyst carrier, and obtain a finished catalyst unit through drying and calcination.
2. A method for preparing a denitration catalyst according to claim 1, characterized in that: When the preparation method adopts an integral extrusion catalyst, the step S4 specifically comprises: S41, pouring the mixed solution B into titanium dioxide and continuing to stir to obtain a uniform mass structure, and then sequentially performing aging, mold extrusion molding, drying, and calcination to obtain a finished catalyst unit.
3. A method for preparing a denitration catalyst according to claim 1, characterized in that: When the preparation method adopts an impregnation catalyst, the step S4 specifically comprises: S42, immersing the catalyst substrate into the mixed solution B through ultrasonic impregnation, and then taking out, drying, and calcining in sequence to obtain a finished catalyst unit.
4. A method for preparing a denitration catalyst according to claim 1, characterized in that: The dispersant A is at least one of fatty alcohol polyoxyethylene ether, polyethylene glycol, HPMA, and monoethanolamine.
5. A method for preparing a denitration catalyst according to claim 4, characterized in that: The step S1 specifically includes: S11. Mix AMV and triethanolamine, and add deionized water to fully dissolve to prepare an AMV solution. S12, adding AMT to deionized water to fully dissolve AMT to prepare an AMT solution; S13, mixing ammonium paramolybdate and phosphoric acid, adding deionized water to fully dissolve to prepare an ammonium metamolybdate solution.
6. A method for preparing a denitration catalyst according to claim 5, characterized in that: In the step S11, the mass ratio of triethanolamine to active ingredient is 1-50:
100.
7. A method for preparing a denitration catalyst according to claim 5, characterized in that: In the step S2, the mass ratio of triethylenediamine to active ingredient is 1-50:
100.
8. A method for preparing a denitration catalyst according to claim 5, characterized in that: In the step S2, the mass ratio of dispersant A to active ingredient is 1-50:
100.
9. A method for preparing a denitration catalyst according to claim 4, characterized in that: The dispersant A is HPMA.
10. A method for preparing a denitration catalyst according to claim 1, characterized in that: In step S3, the mixed solution A is added to the AMV solution, and the mixture is stirred at 40° C. to form a mixed solution B.